Experimental Study on Strain Penetration Effects in Fixed-End Rotation of RC Beam-Column Connections with High-Strength Reinforcement - Ling Li; Wenzhong Zheng; Ying Wang; Junke Ma (Advances in Materials Science and Engineering)
The additional fixed-end rotation resulting from the strain penetration of longitudinal reinforcement in a reinforced concrete beam-column connection is a crucial factor for the plastic hinge rotation capacity. When it comes to high-strength reinforcement, the effects of strain penetration on fixed-end rotation become more obvious because of the increase in yield strength. In this study, 42 beam-column connections with high-strength hot rolled ribbed bars were designed and tested under monotonic loading at the beam end. The test results show that the rebar strains gradually decrease from the critical section towards the beam-column connection, thereby proving the existence of strain penetration in the beam-column connection. The slippage of the embedment reinforcement at the beam-column interface and additional fixed-end rotations were obtained from the test results. In addition, a parametric study involving the yield strength and diameter of reinforcement, concrete tensile strength, and embedment length in the beam-column connection was performed to investigate the effects of various parameters on the additional fixed-end rotation. Finally, a new simple and practical calculation model for predicting the additional fixed-end rotation was proposed. The prediction shows good agreement with the experimental results.